HEGEMONY OF POWER AND RESISTANCE IN THE FILM ARRIHLAH: A GRAMSCIAN LITERARY SOCIOLOGY APPROACH - Muhammad Algi Fari; Yani Heryani; Mawardi (Universitas PGRI Palembang, 2025)
This research investigates the dynamics of power hegemony and resistance in the animated film Ar-Rihlah, drawing on Antonio Gramsci’s theory of hegemony to explore both consensual and coercive mechanisms of domination. Employing a descriptive-analytical method within a literary sociology framework, the study analyzes selected scenes, dialogue, and visual elements through textual and symbolic interpretation. Findings reveal two main hegemonic strategies: consensual hegemony, manifested through moral posturing, deceptive diplomacy, and ideological imagery; and coercive hegemony, conveyed through violence, intimidation, and militarized spectacle. In contrast, three counter-hegemonic responses emerge: physical defiance, spiritually rooted moral resistance, and divine or supernatural intervention. This study offers interdisciplinary relevance across literary criticism, cultural and Islamic studies, media analysis, and animation scholarship. Its originality lies in applying Gramsci’s hegemony theory to the animated depiction of Islamic historical narratives, highlighting how visual storytelling communicates ideological power and resistance. By bridging classical sociopolitical theory with contemporary animated media, the research provides novel perspectives on the cultural functions of Islamic animation as both a pedagogical and ideological tool.